Acute Myocardial Infarction During the COVID-19 Pandemic: An Update on Clinical Characteristics and Outcomes - Toscano, Olga; Cosentino, Nicola; Campodonico, Jeness; Bartorelli, Antonio L.; Marenzi, Giancarlo (Frontiers in Cardiovascular Medicine, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) has rapidly become a worldwide pandemic. On top of respiratory complications, COVID-19 is associated with major direct and indirect cardiovascular consequences, with the latter probably being even more relevant, especially in the setting of time-dependent cardiovascular emergencies. A growing amount of data suggest a dramatic decline in hospital admissions for acute myocardial infarction (AMI) worldwide during the COVID-19 pandemic, mostly since patients did not activate emergency medical systems because hospitals were perceived as dangerous places regarding the infection risk. Moreover, during the COVID-19 pandemic, AMI patients had a significantly higher in-hospital mortality compared to those admitted before COVID-19, potentially due to late arrival to the hospital. Finally, no consensus has been reached regarding the most adequate healthcare management pathway for AMI and a shared guidance on how to handle AMI patients during the pandemic is still needed. In this review, we will provide an update on epidemiology, clinical characteristics, and outcomes of AMI patients during the COVID-19 pandemic, with a special focus on its collateral cardiac impact.